2020
DOI: 10.1002/jbt.22433
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin and juglone inhibit inflammatory molecules to induce apoptosis in colon cancer cells

Abstract: Colorectal cancer (CRC) is the third most common fatal cancer. Indomethacin, a nonsteroidal anti-inflammatory drug, is known to reduce the occurrence of CRC.This study evaluated the potential anticolon cancer effects of juglone (5-hydroxy-1,4-naphthoquinone) in combination with indomethacin. Human colon adenocarcinoma cells (HT29) were subjected to treatment with indomethacin, juglone, and a combination of both. Morphological analysis, cell cycle regulation, and dual staining using acridine orange and ethidium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 47 publications
2
20
0
Order By: Relevance
“…The amplification of apoptosis and the overall antitumor effect of both COX-1 and COX-2 inhibitors have been repeatedly described for a variety of transformed cells. For example, a non-selective COX inhibitor used in this study, indomethacin, suppressed the growth of human colon adenocarcinoma cells [15], MNNG/HOS osteosarcoma cells [16], human H4 and U87 glioma cells [17], and many other cell lines. The proapoptotic effect of COX inhibitors is associated with both reduced COX catalytic activity and inhibition of PGE2 synthesis, even with COX-independent mechanisms [18,19].…”
Section: Discussionmentioning
confidence: 92%
“…The amplification of apoptosis and the overall antitumor effect of both COX-1 and COX-2 inhibitors have been repeatedly described for a variety of transformed cells. For example, a non-selective COX inhibitor used in this study, indomethacin, suppressed the growth of human colon adenocarcinoma cells [15], MNNG/HOS osteosarcoma cells [16], human H4 and U87 glioma cells [17], and many other cell lines. The proapoptotic effect of COX inhibitors is associated with both reduced COX catalytic activity and inhibition of PGE2 synthesis, even with COX-independent mechanisms [18,19].…”
Section: Discussionmentioning
confidence: 92%
“…Recently, the potential antiproliferative effect in colorectal cancer of juglone in combination with indomethacin was investigated: the study showed superiority of the two-drug combination, whilst treatment with juglone alone was not as effective as with indomethacin [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…When it comes to patients who have already developed colorectal cancer, data concerning clinical usefulness of NSAIDs are rarer; use of aspirin seems to improve survival particularly in patients with colorectal cancer harbouring PIK3CA mutations [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism of this process is due to increased levels of COX-2 and prostaglandin E2 (PGE 2 ) [4][5][6][7] that promote proliferation, migration, invasion, and cell adhesion [8,9]. According to these facts, medication with NSAIDs was associated with decreased risk of certain cancer types, particularly gastrointestinal tract cancers (gastric or colorectal cancer), lung, breast, and prostate cancers [10][11][12][13][14]. Clinical and pharmacoepidemiological studies provide evidence that aspirin and other cyclooxygenase-2 enzyme inhibitors lower recurrence of colorectal cancer by about 20% [12,15,16].…”
Section: Anticancer Activity Of Nsaidsmentioning
confidence: 99%